"My name is midori". O zbrodniczych akuninach ("Unless" Borysa Akunina) = "My name is midori". About criminal akunins (("Unless" by Boris Akunin) - Prażuch, Karolina; Radziszewski, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The theme of this article is "Unless", a crime story by Boris Akunin, which takes place in 2004, andwhose protagonists, Misha, is a Russian living in the USA. The investigation of his suicide, whichhe commits in New York's Greenwood Cemetery, leads to a mysterious femme fatale. The analysisof Akunin?s essays collected in Cemetery stories, makes it possible to think that the femme fatale isthe notorious Lola Montez, who lived in the 19th century.
Keywords: Akunin, Boris (pseud.), Čhartišvili, Grigorij Šalvovič (1956- ); powieść kryminalna; literatura rosyjska; 21 w.